Application of LMS, Google Meet, and PhET Interactive Simulations as an Effort to Develop Student Creativity and Communication Skills in Waves and Optics lectures - Hikmawati, Hikmawati; Kosim, Kosim; Ayub, Syahrial (Journal of Science and Science Education, 2024)
This research aims to describe the application of the Learning Management System (LMS), Google Meet, and PhET interactive simulations as an effort to develop student creativity and communication skills in Waves and Optics lectures. This research, which uses a one shot case study design, was carried out in the 2023 academic year (odd semester) at the Physics Education Study Program, FKIP, University of Mataram. The research subjects included all University of Jambi students who took Waves and Optics courses with code 133414. These students took part in the Independent Campus program, namely the Independent Student Exchange (ISE), with a total of 20 people. The instrument for creativity uses a product assessment sheet uploaded to the LMS, namely SPADA Unram, while the instrument for communication skills uses an observation sheet during product presentations via Google Meet. The product in question is a paper that discusses a particular topic accompanied by data from PhET interactive simulations. The assessment score for each indicator for both creativity and communication skills uses a scale of 4. The scores for creativity and communication skills are expressed in percentage form. The research results show that the average score for student creativity is 83.0 (B+ criteria), while student communication skills are 86.8 (A criteria). The lowest score in the creativity aspect is 75 (B criteria) with the highest score being 90 (A criteria). The lowest score in the communication skills aspect is 80 (B+ criteria) with the highest score being 90 (A criteria). Thus, implementing LMS, Google Meet, and PhET interactive simulations can be an alternative in developing creativity and communication skills. Optimizing learning media needs to be done to produce better creativity and communication skills